Primary Hepatic Neuroblastoma in a 19-month-old Child: A Case Report - Dimic, Jovana; Škorić, Dejan; Sretenović, Aleksandar; Đuričić, Slaviša (Medical Research, 2022)
Introduction. The most common site of neuroblastoma is the adrenal medulla. Neuroblastoma arising in solid organs other than the sympathetic nervous system is extremely rare. Liver neuroblastomas are usually metastatic lesions, particularly from stage 4S adrenal neuroblastoma. Patient review. We report the first case of primary hepatic high-risk neuroblastoma diagnosed in a child older than 12 months. The patient received multimodal oncology treatment including chemotherapy, surgery, bone marrow transplantation, radiotherapy, and immunotherapy. Also, regional deep hyperthermia was applied. Despite the timely diagnosis, the tumor was refractory to intensive treatment and the patient died 2.5 years after the diagnosis. Conclusion. The differential diagnosis of primary malignant liver tumors in pediatric patients should include neuroblastoma, especially in tumors with atypical clinical presentation. The reports of similar cases in the future may contribute to better tumor biology understanding and facilitate clinical management.